What Factors Explain Institutionalization? A Qualitative Comparative Analysis of Participatory Budgeting in Italian Big Cities - Domenico Andrea Schiuma (Italian Political Science, 2025)
Since its first implementation in Porto Alegre, Brazil, in 1989, Participatory Budgeting (PB) has probably become the most widespread participatory policy in the world. Though it sometimes succeeds in becoming an ordinary government tool, it usually fails to do so. Given that it has been around since 1989, there is today enough empirical and theoretical knowledge to try to build explanatory models for the (non)institutionalization of PB. This work relies on Qualitative Comparative Analysis (QCA) to detect the combinations of explanatory conditions leading to the presence or absence of the outcome ‘PB institutionalized as of 2023’ in a set of fourteen big Italian cities. The paper first proposes a new operationalization of ‘institutionalization’, used to find out in which big Italian cities PB is institutionalized. Then, based on previous literature and a specific knowledge of the Italian case, this work proposes five conditions which may have explanatory power with regard to the presence or absence of the outcome. These conditions are measured and calibrated. Necessary and/or sufficient (combinations of) conditions for the presence and absence of the outcome are then analysed. Next, these results are used to hypothesize possible mechanisms behind the institutionalization of PB in the cities involved. Finally, the potential and limitations of this study are discussed in the last section.